Pesticides, nonylphenols and polybrominated diphenyl ethers in marine bivalves from France: A pilot study. (November 2021) - Lerebours, Adélaïde; Bathie, Marguerite; Receveur, Justine; Jézéquel, Ronan; Dubillot, Emmanuel; Brunello, Pascal; Barbier, Pierrick; Le Floch, Stéphane; Thomas, Hélène
Abstract: The present pilot study aimed to provide an overview of organic contaminant concentration levels in the littoral ecosystems of the Pertuis seas. The study determined the concentrations of twenty-nine pesticides, six nonylphenols and seven polybrominated diphenyl ethers (PBDEs) in sediments, seawater, Pacific oysters and blue mussels. Oysters accumulated a higher number of pesticides than blue mussels. Indeed, alpha BHC (0.60–0.72 ng/g, ww), chlorfenvinphos (1.65–2.12 ng/g, ww), chlorpyrifos (0.79–0.93 ng/g, ww), chlortoluron (2.50–4.31 ng/g, ww), metolachlor (up to 0.38 ng/g, ww) and parathion (0.56–0.69 ng/g, ww) were quantified in oysters whereas only alpha BHC (0.24–0.31 ng/g, ww), was quantified in mussels. The present results also revealed that the POPs detected in water or sediments were not ultimately found accumulated in bivalves. Other molecules such as methylparathion and BDE47 were quantified in sediments. These molecules, BDE99 and one nonylphenol (OP2OE) were quantified in seawater. Finally, the comparison with the available environmental guidelines showed that the values measured were at concentrations not considered to cause adverse effects at the populations' level except for chlortoluron in seawater (15–50 ng/L). Highlights: Pacific oysters accumulated a greater number of pesticides than blue mussels The POPs detected in seawater or sediments were not ultimately found in bivalves The concentrations of 42 organic pollutants were very low in sediment, seawater and biota